Middle Ear Pressure Changes after Adenotonsillectomy and Myringotomy in Patients with Otitis Media with Effusion (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Otitis media with effusion(OME) is a common ear problem among children characterized by accumulation of secretion in the middle ear. The pathophysiology of OME is negative pressure due to eustachian tube dysfunction. In children adenoid enlargement is associated with enlargement of the tonsils. Surgical treatment is advocated when conservative treatment fails. Surgical treatment consists of adenotonsillectomy with myringotomy. Negative middle ear pressure is expected to improve after surgical intervention.Objectives: To see the pressure changes after surgical treatment of OME.Methods: Among 68 subjects with OME, 88 ears were operated. Adenotonsillectomy was done in all subjects. In addition myringotomy was done in 65 ears and myringotomy with grommet insertion was done in 23 ears. In post-operative period all patient were followed up at end of 1 month, 3 month and 6 month with tympanometry.Results: Pre operatively type B tympanogram was 67(76.13%) whereas type Atympanogram was 0(0%). At end of 6 month type A curve was 49(61.27%) and type B tympanogram was 9(11.25%) that indicates improvement of middle ear function after operation.Conclusion: Tympanometric improvement was significant after 6 month of surgery.Bangladesh J Otorhinolaryngol 2022; 28(1): 22-28